(untitled) (Historia, 2021)
The calling of Katie Makanya is one of the most engrossing and heart-rendering books I have had the privilege of reading. It is the life story of Katie Makanya from her youth in the eastern Cape to her death at the age of 83 in 1955. It is based on interviews she had with Margaret McCord for whose father, Dr. James McCord, Katie had worked for 35 years as interpreter, dispenser and assistant in Natal.